To investigate the relationship between substrates of the N-end rule pathway and genes regulated by ‘GCCGCC’ cis-elements in Arabidopsis thaliana - Prasad, Geeta (2016)
The N-end rule pathway of targeted proteolysis is regulated by Group VII ethylene response factors (ERFVII’s). The aim of this research work was to analyse the relationship between substrates (ERFVII’s) of the N-end rule pathway and genes, which have promoters containing a double ‘GCCGCC’ Ethylene-Responsive Element Binding Protein (EBP) cis-element. Several genes were identified containing double EBP elements. Cloning and transformation of the promoters from five of these genes (PYL, ERD4, AT1G14810, AT3G13440 and AT5G44420) carrying two copies of the GCC-boxes present in the 5' UTR (5’ untranslated region) or promoter region was conducted into Arabidopsis wild-type (Col-0) and prt6-1 mutant plants. Expression driven by these promoters in the leaves and flowers of transgenic plants was analysed through GUS staining to reveal promoter activities. Enhanced promoter activity was seen in prt6-1 lines (mutated in the E3-ligase of the N-end rule pathway) in comparison to Col-0. Further, cDNA of leaves and flowers of Col-0 and prt6-1 were analysed by q-RT-PCR (quantitative real-time PCR) for expression of PYL7, ERD4, AT1G14810, AT3G13440; t-test analysis showed a significant difference (p-value<0.05) only in leaves of Col-0 and prt6-1 for PYL7. Analysis of the genetic relationship between N-end rule pathway and genes containing GCC-boxes was also performed by analysing double mutant combinations of prt6-1 and mutants of genes containing the EBP elements (pyl7prt6-1, erd4prt6-1 and abi5prt6-1) and Col-0 under different concentration of salt to determine the effect of stress due to salinity on the regulation of genes. At 125mM salt concentration significant difference was identified in highest number of mutant lines in comparison to Col-0. An analysis of the in-vivo binding of the ERFVII RAP2.3 to the promoter of GCC-boxes containing genes was performed through Chromatin Immuno-precipitation assay (ChIP). The t-test analysis on qChIP-PCR data indicated significant difference between IgG and HA-IPs for both ABI5 and PYL7 performed on normoxic 35S:MA-RAP2.3-HA in Col-0 line. Further, in-vivo localization of ERFVII’s HRE1 and RAP2.2 conditional stability was analysed using promERFVII’s:MC/MA-ERFVII’s-YFP constructs in Col-0 and prt6-1. This thesis suggests that genes PYL7, ERD4, AT1G14810, AT3G13440 that have double ‘GCCGCC’ EBP elements are downstream targets of the N-end rule pathway. Further analysis via ChIP suggests that RAP2.3 interacts with the ‘GCCGCC’ binding site of promoters in the ABI5 and PYL7 genes, however further work is needed to confirm this. Additionally, sub-cellular localization of promERFVII’s:MC/MA-ERFVII’s-YFP studies suggest the location of HRE1 and RAP2.2 in nuclei of early stage root tips studied on 4-days old etiolated seedlings.